2020
DOI: 10.1101/2020.06.04.133728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RAS-inhibiting biologics identify and probe druggable pockets including an SII-α3 allosteric site

Abstract: Telephone +44 (0)113 34 37099 † These authors contributed equally.ABSTRACT RAS mutations are the most common oncogenic drivers across human cancers, but there remains a paucity of clinically-validated pharmacological inhibitors of RAS, as druggable pockets have proven difficult to identify. We have identified two RASbinding Affimer proteins, K3 and K6, that inhibit nucleotide exchange and downstream signalling pathways with distinct isoform and mutant profiles. Affimer K6 is the first biologic to bind in the S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…We identified 699 human KRAS (N=421), HRAS (N=268), and NRAS (N=10) structures from 392 PDB entries (some entries contain multiple copies of the structure, sometimes in different conformations). Subsequently, we created an automated system for annotating RAS structures by their molecular contents, including their mutation status, nucleotide state ("3P" for GTP or any triphosphate analog, "2P" for GDP, and "0P" for nucleotide-free), bound proteins (effector, GAP, GEF CDC25 and REM domains, designed protein "binders" such as an Affimer 22 or DARPin 23,24 , nanodiscs, and others), small molecule inhibitor sites (SP12, SP2, and others), and whether the α4α5 homodimer is present in the protein crystal (only X-ray structures). In following subsections, we identify the conformations of SW1 and SW2 in the prepared RAS structures and associate these conformations with the described molecular contents to define an expanded RAS conformational classification (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 699 human KRAS (N=421), HRAS (N=268), and NRAS (N=10) structures from 392 PDB entries (some entries contain multiple copies of the structure, sometimes in different conformations). Subsequently, we created an automated system for annotating RAS structures by their molecular contents, including their mutation status, nucleotide state ("3P" for GTP or any triphosphate analog, "2P" for GDP, and "0P" for nucleotide-free), bound proteins (effector, GAP, GEF CDC25 and REM domains, designed protein "binders" such as an Affimer 22 or DARPin 23,24 , nanodiscs, and others), small molecule inhibitor sites (SP12, SP2, and others), and whether the α4α5 homodimer is present in the protein crystal (only X-ray structures). In following subsections, we identify the conformations of SW1 and SW2 in the prepared RAS structures and associate these conformations with the described molecular contents to define an expanded RAS conformational classification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we found that binders with preference for targeting 2P structures bind to multiple RAS interfaces; these include Affimers K3 (SP2 site), K6 (SP12 site), and K69 (α4α5 interface) as we all the DARPin K27 (SP12 site). Of the 2P-interacting binders, Affimer K3 and DARPin K27, which both function to block nucleotide exchange (41,43), bind to the SW1 conformation, Y32in.2P-OFF, and SW2 conformation, Y71out.2P-BINDER (hence the chosen conformational label) ( Figs. 3K and 3L ).…”
Section: Resultsmentioning
confidence: 99%
“…Through fragment-based screening, a series of indole-based inhibitory compounds were found to bind to SI/II-P, 8,9 a cryptic pocket located between the a2 helix and the central b-sheet. A variety of other smallmolecule and macromolecule inhibitors were also identified in subsequent studies, [10][11][12][13] binding to the same cryptic pocket in both GDP-and GTP-bound states. Notably, some of their affinities have reached the nanomolar range, demonstrating the druggability of SI/II-P. 10,13 In a 2013 landmark study on allele-specific inhibition against Ras(G12C), Shokat and coworkers discovered a series of electrophilic compounds that can covalently attack the mutant cysteine and bind within another cryptic pocket (SII-P) located beneath the switch II region.…”
Section: Introductionmentioning
confidence: 97%